Diverse Epitope Specificity, Immunodominance Hierarchy, and Functional Avidity of Effector CD4 T Cells Established During Priming Is Maintained in Lung After Influenza A Virus Infection - Richards, Katherine A.; DiPiazza, Anthony T.; Rattan, Ajitanuj; Knowlden, Zackery A. G.; Yang, Hongmei; Sant, Andrea J. (Frontiers in Immunology, 2018)
One of the major contributions to protective immunity to influenza viruses that is provided by virus-specific CD4 T cells is delivery of effector function to the infected lung. However, there is little known about the selection and breadth of viral epitope-specific CD4 T cells that home to the lung after their initial priming. In this study, using a mouse model of influenza A infection and an unbiased method of epitope identification, the viral epitope-specific CD4 T cells elicited after infection were identified and quantified. We found that a very diverse specificity of CD4 T cells is primed by infection, including epitopes from hemagglutinin, neuraminidase, matrix protein, nucleoprotein and non-structural protein-1. Using peptide-specific cytokine EliSpots, the diversity and immunodominance hierarchies established in the lung-draining lymph node was compared with specificities of CD4 T cells that home to the lung. Our studies revealed that CD4 T cells of all epitope specificities identified in peripheral lymphoid tissue home back to the lung and that most of these lung-homing cells are localized within the tissue rather than the pulmonary vasculature. There is a striking shift of CD4 T cell functionality that enriches for IFN-γ production as cells are primed in the lymph node, enter the lung vasculature and finally establish residency in the tissue, but with no apparent shifts in their functional avidity. We conclude that CD4 T cells of broad viral epitope specificity are recruited into the lung after influenza infection, where they then have the opportunity to encounter infected or antigen-bearing antigen presenting cells.